RESPONSIBILITY FOR MATERIAL DEFICIENCIES OF GOODS, WITH REFERENCE TO ORGANIC PRODUCT - Rajnović, Ljiljana Dušan; Mihailović, Nenad; Cico, Snežana (Economics of Agriculture, 2023)
In this paper, the authors discuss the responsibility for material deficiencies of goods, with reference to the organic agriculture products, given the specific and highly demanding production system and the growing demand for organic products in developed countries and in Serbia. An integral part of everyday life is the risk that the goods purchased are more or less materially defective. Organic production methods involve the usage of natural processes and substances, and limit or completely eliminate the use of synthesized agents. Also, producers inevitably suffer from various external influences. The desire of consumers is to buy products which use natural ingredients that are obtained on the basis of natural procedures. Research in this paper has shown that in the creation of an organic product may occur material defects that more or less impair its essence. Therefore, this paper analyzes such shortcomings and also recommends how customers can act when they find themselves in this situation.